Cost Investigation on Green Fuel Production from Manila Grass Mixed with Crop Residues and GHG Emission Mitigation - Thanarak, Prapita; Chaiyote, Chuleeporn (Asian Health, Science and Technology Reports, 2012)
Green fuel is a combination of methods to solve the problems related to production, transport, storage and use of biomass for household energy. This article discusses the study of green fuel production from manila grass mixed with crop residues, using cassava mucilage as a binder. The fuel is formed in the form of briquettes, which is compressed, easy to handle and takes little volume for storage. Experiments were carried out to determine heating value and other physico-chemical characteristics of the fuels. The results show that the 5 formulae of grass and cassava mucilage have heating values in the range 3,761.14 - 3,941.65 kcal/kg. The content of fixed carbon, volatile matter and ash were between 32.78 - 24.56%, 48.86 - 59.29% and 8.52 - 10.69% respectively. Fixed carbon and ash decreased when the proportion of cassava mucilage was increased. Concerning physical characteristics, it is found that mixing ratio between grass and cassava mucilage of 1:2 to 1:3 can make briquettes quite well. The cost increased when the proportion of cassava mucilage increased; the lowest was 15.58 baht/kg from ratio 1:1, the highest was 18.10 baht/kg from ratio 1:3. The results of green fuel from grass mixed with crop residues (rice straw and sugar cane leaf) show that heating values of fuel were between 3,623.15 - 3,901.50 kcal/kg and increase when increasing the content of grass. Fixed carbon increased when increasing the content of grass. The content of fixed carbon was found to be between 22.99 - 25.12%, the highest was for ratio 80:20 of grass mixed with rice straw. The percentage of volatile matter decreased while increasing the content of grass. Volatile matter was found to be between 58.34 - 61.44%, the highest was for ratio 70:30 of grass mixed with rice straw. Ash was between 8.96 - 11.71%, increasing when the content of grass increase. The costs for grass mixed with rice straw of 80:20 at 3,849.95 kcal/ kg, were between 17.25 baht/kg and decreased increasing the proportion of grass. The GHG emission mitigation is 1.5169 kgCO 2 / kg. The costs for grass mixed with sugar cane leaf, at 3,901.50 kcal/kg were between 16.75 baht/kg, the lowest for ratio 80:20. The GHG emission mitigation is 1.5367 kgCO 2 /kg.